Histone Modifier Differentially Regulates Gene Expression and Unravels Survival Role of MicroRNA-494 in Jurkat Leukemia - Jayaraman, Arathi; Zhou, Tong; Jayaraman, Sundararajan (MicroRNA, 2021)
Background: Although the protein-coding genes are subject to histone hyperacetylation- mediated regulation, it is unclear whether microRNAs are similarly regulated in the T cell leukemia Jurkat. Objective: To determine whether treatment with the histone modifier Trichostatin A could concurrently alter the expression profiles of microRNAs and protein-coding genes. Methods: Changes in histone hyperacetylation and viability in response to drug treatment were analyzed, respectively, using western blotting and flow cytometry. Paired global expression profiling of microRNAs and coding genes was performed and highly regulated genes have been validated by qRT-PCR. The interrelationships between the drug-induced miR-494 upregulation, the expression of putative target genes, and T cell receptor-mediated apoptosis were evaluated using qRT-PCR, flow cytometry, and western blotting following lipid-mediated transfection with specific anti-microRNA inhibitors. Results: Treatment of Jurkat cells with Trichostatin A resulted in histone hyperacetylation and apoptosis. Global expression profiling indicated prominent upregulation of miR-494 in contrast to differential regulation of many protein-coding and non-coding genes validated by qRT-PCR. Although transfection with synthetic anti-miR-494 inhibitors failed to block drug-induced apoptosis or miR-494 upregulation, it induced the transcriptional repression of the PVRIG gene. Surprisingly, miR-494 inhibition in conjunction with low doses of Trichostatin A enhanced the weak T cell receptor- mediated apoptosis, indicating a subtle pro-survival role of miR-494. Interestingly, this prosurvival effect was overwhelmed by mitogen-mediated T cell activation and higher drug doses, which mediated caspase-dependent apoptosis. Conclusion: Our results unravel a pro-survival function of miR-494 and its putative interaction with the PVRIG gene and the apoptotic machinery in Jurkat cells.
Keywords: epigenetics